Scientometric Analysis of Political Documents of Overton: Open Government Data Case Study - Forough Rahimi; Farshid Danesh (مجله علم‌سنجی کاسپین)
Background and aim: Open Government Data is essential for today's civil society. The aim of this article is scientometric analysis of political documents based on open government data in Overton database. Materials and methods: This applied research was conducted based on scientometric indices and content analysis. Data from 2007 to 2023 were extracted from the Overton database. The research community includes 2493 documents related to open government data. The data were analyzed using Chi-square, Spearman's correlation coefficient, and Mann–Whitney U tests. Data analysis was conducted using SPSS Statistics 24. Findings: The Organization for Economic Cooperation and Development (OECD), with 514 citations, and the Guardian News Agency, with 291 citations, stand out as the most effective organizations and news agencies in the present research. Furthermore, a notable positive correlation exists between GDP and the quantity of government documents concerning open government data at the national level. Additionally, a significant positive yet weak correlation exists between SJR and the number of citations obtained from government documents. Conclusion: In recent years, there has been a significant increase in government publications on open government data. This is in line with the global open government paradigm. The results showed that human activities, economy, technology, innovation, and governance have had the most significant impact on issues related to government documents published as open government data.